Efektivitas Strategi Pembelajaran IPS dalam Meningkatkan Pemahaman Kegiatan Ekonomi Siswa Sekolah Dasar: Studi Literatur - Najwa Naumira; Mitta Pebri; Syahidah Awaliyah Bintang; Nurul Ilmi Nasution; M. Hafiz Alfiandi; Eka Yusnaldi (Journal Pendidikan Ilmu Pengetahuan Sosial, 2024)
The teaching of Social Sciences (IPS) in elementary schools, particularly the material on economic activities, plays an important role in shaping students' understanding of social and economic life. However, many students have difficulty understanding basic economic concepts. Therefore, the implementation of effective learning strategies is highly necessary. Various studies show that appropriate learning strategies can enhance students' understanding of economic activities. This article aims to examine the effectiveness of various IPS learning strategies applied to enhance elementary school students' understanding of economic activities. The problem formulation examined in this article is: 1) How effective are IPS learning strategies in improving elementary school students' understanding of economic activities? 2) What are the challenges faced in its implementation? 3) What factors influence the success of the learning strategy? The method used in this article is a literature review. And using narrative analysis in analyzing the sources. The brief conclusion of this article is that there are at least 4 strategies to improve elementary school students' understanding of economic activities. And in applying them, there are also several problems and challenges. And external and internal factors greatly influence the success of these strategies.